Analysis Of Students’ Languange Errors – ( Psycholinguistic Study Of L2 Learners) - Wulandari lubis; MH Batubara (Yayasan Al-Afif, 2025)
This study aims to provide an in-depth analysis of the second language (L2) usage patterns among 15 first-semester English Education (Tadris Bahasa Inggris) students at STAIN Madina and its impact on their competence in Mandailing as their first language (L1). Using a descriptive qualitative approach, data were collected through direct observation, semi-structured interviews, and recorded conversations in both academic and non-academic settings. The findings reveal that the students predominantly use Indonesian (L2) in various communication contexts, including campus interactions, social engagement, and digital media use. This heavy reliance on L2 has led to a decline in their Mandailing language competence, particularly in vocabulary mastery, fluency, and sensitivity to L1 linguistic structures. Several factors contribute to this decline. The campus and social environment prioritize Indonesian, limiting opportunities for Mandailing use. Additionally, family communication patterns that rely more on L2 reduce the Mandailing input students receive from an early age. Internal factors such as low motivation to maintain their heritage language, which is often viewed as less relevant in academic and modern social settings also accelerate the language shift. These findings indicate early signs of language shift among first-year university students at STAIN Madina. Therefore, language revitalization efforts and stronger involvement from families and educational institutions are necessary to preserve the Mandailing language as an essential cultural identity.